2011
DOI: 10.1007/s13277-011-0205-2
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase Cα suppresses the expression of STC1 in MDA-MB-231 breast cancer cells

Abstract: Several protein kinase C (PKC) isoforms have been shown to influence different cellular processes that may contribute to the malignancy of breast cancer cells. To obtain insight into mechanisms mediating the PKC effects, global gene expression was analyzed in MDA-MB-231 breast cancer cells in which PKCα, PKCδ or PKCε had been down-regulated with siRNA. Gene set enrichment analyses revealed that hypoxia-induced genes were enriched among genes that increased in PKCα-down-regulated cells. The STC1 mRNA, encoding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 42 publications
(48 reference statements)
1
10
0
Order By: Relevance
“…Hypoxia-induced genes make cells more tolerant to the unfavorable conditions in certain cancer cell lines (24,25). In accordance with studies in other cell lines (9,(26)(27)(28)(29), it was demonstrated that STC1 could be stimulated in hypoxic environments. However, the roles of STC1 under hypoxic conditions are inconsistent according to different cell types.…”
Section: Discussionsupporting
confidence: 77%
“…Hypoxia-induced genes make cells more tolerant to the unfavorable conditions in certain cancer cell lines (24,25). In accordance with studies in other cell lines (9,(26)(27)(28)(29), it was demonstrated that STC1 could be stimulated in hypoxic environments. However, the roles of STC1 under hypoxic conditions are inconsistent according to different cell types.…”
Section: Discussionsupporting
confidence: 77%
“…Although most of studies have focused on the calcium-regulating functions of STC1, increasing evidence suggests that STC1 may also play a major role in carcinoma. High expression of STC1 was frequently detected in human tumor samples of hepatocellular carcinoma (HCC) [16], colorectal cancer [17], lung adenocarcinoma [9], breast cancer [18, 19] and thyroid carcinomas [20], however, low expression of STC1 was found in tumor-derived ovarian epithelial cells [21]. Our previous studies have shown that STC1 is on the decrease in cervical cancer cells for the first time, and that it suppresses cellular multiplication and metastasis of cervical cancer cells likely through NF-κB P65 protein [22].…”
Section: Introductionmentioning
confidence: 99%
“…Western blot was performed as described in a previous publication [ 37 ]. Primary antibodies used were anti-PKCδ (1:500, Santa Cruz), anti-Smac (1:500, Santa Cruz), anti-Actin (1:2000, MP Biomedicals), anti-HSV (1:1000, Novagen), anti-GST (1:2000, GE Healthcare) and anti-GFP (1:1000, Invitrogen).…”
Section: Methodsmentioning
confidence: 99%